Low Hemoglobin Levels and Hypo‐Responsiveness to Erythropoiesis‐Stimulating Agent Associated With Poor Survival in Incident Japanese Hemodialysis Patients. Issue 5 (25th February 2014) - Akizawa, Tadao; Saito, Akira; Gejyo, Fumitake; Suzuki, Masashi; Nishizawa, Yoshiki; Tomino, Yasuhiko; Tsubakihara, Yoshiharu; Akiba, Takashi; Hirakata, Hideki; Watanabe, Yuzo; Kawanishi, Hideki; Bessho, Masami; et al.
Abstract Although erythropoiesis‐stimulating agents (ESAs) are effective at treating anemia, the association between hemoglobin (Hb) levels and survival is still unclear, especially for the incident Japanese hemodialysis (HD) population. The Japan Erythropoietin Treatment (JET) Study is an open multi‐center, prospective, observational study designed to evaluate the relationship between the maintenance of Hb levels and new HD patient prognosis after the first administration of epoetin beta. Landmark analyses were performed to examine the relationship between Hb levels at 6 months and survival. Among a total of 10 310 patients, 6631 completed the initial 6 months of epoetin beta treatment (induction phase) and were followed up for a further 2.5 years (maintenance phase). Three‐year survival rate of patients with <9 g/dL Hb levels after 6 months was 74.1%, which was significantly lower than 89.3% for patients with Hb levels 10 to 11 g/dL; the adjusted hazard ratio (HR) was 2.08 (95% CI, 1.57–2.77; P < 0.0001). Moreover, the 3‐year survival rate for poor responders defined by Hb levels <10 g/dL and weekly epoetin beta doses ≥9000 IU during the induction phase was 71.6%, which was significantly lower than 89.4% for the group, which had Hb levels 10 to 11 g/dL excluding poor responders and those with excursion; the HR was 1.71 (95% CI, 1.13–2.60; P = 0.0118). Adverse events related to the treatment were reported in 71 of 10 310 patients (0.69%). These findings suggest that the achieved low Hb levels and poor response to ESA therapy are significantly associated with high mortality.